Mould Models Applicable to Wood-Based Materials – A Generic Framework. (October 2017) - Gradeci, Klodian; Labonnote, Nathalie; Köhler, Jochen; Time, Berit
Abstract: This paper systematically reviews mould models that are applicable to wood-based materials. Both similarities and differences are observed with respect to governing factors and their interrelations, methodology, experimental set-ups, substrate and extensiveness, and how the result is communicated. Therefore, a generic framework, representing the general computation procedure of all models, is developed considering the factors that govern mould behaviour. This framework, adapted to each model, is used to structure, evaluate and compare current models. This outline supplemented with a comparison table, revealing the models' extensiveness and differences, establishes a basis to ensure better adequate application of the selected mould model for the case at hand.